Prolactin Level in Polycystic Ovary Syndrome (PCOS): An approach to the diagnosis and management - Davoudi, Zahra; Araghi, Farnaz; Vahedi, Maryam; Mokhtari, Navid; Gheisari, Mehdi (Acta Biomedica Atenei Parmensis, 2021)
Introduction: In spite of the increasing prevalence of polycystic ovary syndrome, there are restricted studies about different features of PCOS. In this study, we evaluate serum prolactin levels in PCOS patients and compare clinical features and hormone levels between patients with hyperprolactinemia and normal levels of prolactin. Methods: Serum prolactin level in 330 PCOS patients were evaluated. If the prolactin levels were normal (equal to or less than 25 ng/ml) the patient was considered normal. If the prolactin levels were >25 ng/ml, then the level was measured by Polyethylene glycol (PEG) precipitation method to detect macroprolactinemia. Furthermore, brain MRI was done in case of hyperprolactinemia to discover pituitary adenoma. Results: Among 330 patients with PCOS, 208 (63.4%) had normal prolactin levels and 122 (37%) patients had hyperprolactinemia. Among hyperprolactinemic patients, 72 (59%) had normal prolactin levels after PEG precipitation and 33 (27%) patients had pituitary adenoma in their brain MRI and 17 (13%) patients were considered as idiopathic hyperprolactinemia with normal MRI. Further, higher levels of LH and LH/FSH ratio and lower estradiol levels were observed in patients with normal prolactin levels. Also, menstrual disorders were more prevalent among patients with pituitary adenoma. Conclusions: Investigating increased level of prolactin in PCOS patients is recommended to detect the causes of hyperprolactinemia, especially macroprolactinemia.